Impact of ellagic acid on adriamycin-induced testicular histopathological lesions, apoptosis, lipid peroxidation and sperm damages - Çeribaşı, Ao; Sakin, F; Türk, G; Sönmez, M; Ateşşahin, A (My University, 2012)
The aim of the present study was to investigate whether ellagic acid (EA) has protective effect on adriamycin (ADR)-induced testicular and spermatozoal toxicity associated with the oxidative stress in male rats. Thirthy-two healthy 8-week-old male Sprague–Dawley rats were equally divided into four groups. The first (EA) group was treated with EA (2 mg/kg/every other day) by gavage. The second (ADR) group received ADR (2 mg/kg/once a week) intraperitoneally, while the combination of ADR and EA was given to the third (ADR + EA) group. The forth (control) group was treated with placebo. At the end of the 8- week treatment period, reproductive organ weights, epididymal sperm parameters, histopathological changes and apoptosis via Bax and Bcl-2 proteins, testicular tissue lipid peroxidation, and antioxidant enzyme activities, were investigated. ADR administration was determined to cause significant decreases in reproductive organ weights, epididymal sperm concentration and motility, plasma testosterone concentration, diameter of seminiferous tubules, germinal cell layer thickness, Johnsen’s testicular score and Bcl-2 positive antiapoptotic cell rate, wherease it caused significant increases in level of lipid peroxidation and glutathione, catalase activity, abnormal sperm rates and Bax positive apoptotic cell rates along with degeneration, necrosis, immature germ cells, congestion and atrophy in testicular tissue when compared with the control group. EA administration to ADR-treated rats provided significant improvements in ADR-induced disturbed oxidant/antioxidant balance, decreased testosterone concentration, testicular apoptosis and mild improvements in the histopathological view of the testicular tissue. However, EA failed to improve decreased reproductive organ weights and deteriorated sperm parameters due to ADR administration. It is concluded that while ADR has direct or indirect (lipid peroxidation) negative effects on sperm structure and testicular apoptosis in rats, EA has protective effects on ADR-induced testicular lipid peroxidation and apoptosis.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Adriamycin Ellagic acid Lipid peroxidation Testicular apoptosis Sperm characteristics